1992
DOI: 10.1148/radiology.184.1.1609078
|View full text |Cite
|
Sign up to set email alerts
|

Simplified percutaneous gastrostomy.

Abstract: By using 16-F self-retaining feeding catheters, fluoroscopically guided percutaneous gastrostomy was performed in 68 consecutive adult patients without the use of gastric fixation devices. Short-term (2-week) follow-up of all patients was available, with 30-day follow-up obtained in 94% of the study group (n = 64). Thirty-day mortality was 12%, with no procedure-related deaths. Major and minor morbidity rates were 4.7% and 7.8%, respectively. The mean procedure time was 7 minutes. These data compared favorably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 0 publications
2
13
0
1
Order By: Relevance
“…This is decreased when compared to other techniques without gastropexy such as 4.7% in Deutsch et al [15] and 6% in Hicks et al [16] and similar to those described in Bell et al [17] at 1.3%. This complication rate also falls within the 1.4-5.9% range described by Covarrubias et al [18].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is decreased when compared to other techniques without gastropexy such as 4.7% in Deutsch et al [15] and 6% in Hicks et al [16] and similar to those described in Bell et al [17] at 1.3%. This complication rate also falls within the 1.4-5.9% range described by Covarrubias et al [18].…”
Section: Discussionsupporting
confidence: 79%
“…There are several documented techniques for placement of gastrostomy catheters without gastropexy, including the use of dilators and peel-away sheaths with a wide array of catheter types [15][16][17]. Trerotola, et al described a single-step balloon dilatation with a large bore peel-away sheath advanced over the balloon prior to gastrostomy tube placement [20].…”
Section: Discussionmentioning
confidence: 99%
“…McLoughlin et al [5] found that the use of T-fasteners when placing primary jejunostomy tubes prevented movement of small bowel loops, and so decreased the risk of volvulus around the jejunostomy catheter; however, other groups have found that large calibre (16-F) catheters may be safely placed without gastric fixation [39]. Indeed, in this same study Deutsch et al [39] proposed that the risk of bleeding may be increased due to the additional needle punctures necessary for the placement of the T-fasteners. In a separate study Moote et al [40] found no significant pericatheter leakage around gastrostomy tubes of various calibres (8-18 F) without routine gastropexy.…”
Section: Gastropexymentioning
confidence: 99%
“…Percutaneous gastrostomy is widely recognized as a safe procedure for providing access for enteral nutrition in patients with unsafe or impossible condition for oral intake, and it has a low risk of complications (1, 2, 3, 4, 5, 6, 7, 8). Percutaneous gastrostomy procedures have been reported to be used in patients who have undergone partial gastrectomy (9, 10, 11, 12, 13, 14).…”
Section: Introductionmentioning
confidence: 99%